Probiotic Saccharomyces cerevisiae var. boulardii supernatant inhibits survivin gene expression and induces apoptosis in human gastric cancer cells. Issue 2 (29th November 2020) - Pakbin, Babak; Pishkhan Dibazar, Shaghayegh; Allahyari, Samaneh; Javadi, Maryam; Farasat, Alireza; Darzi, Sina
Abstract: Natural anticancer drug and compounds with other great benefits are of interest recently due to lower side effects than chemotherapy for cancer treatment and prevention. Different natural and synthetic drugs have been suggested to be used for treatment of gastric cancers, the second deadly cancer worldwide. The aim of this study was to investigate anticancer activity of SBS including inducing apoptosis and inhibition of survivin gene expression in gastric cancer cells. We evaluated cell viability, inducing apoptosis and change in survivin gene expression of EPG85‐257P (EPG) and EPG85‐257RDB (resistant to Daunorubicin, RDB) cell lines under exposure of SBS after 24, 48, and 72 hr. We found that SBS decreased cell viability, induced apoptosis, and reduced survivin gene expression in treated EPG and RDB cells (with the significant IC50 values of 387 and 575 µg/ml after 72 and 48 hr for EPG and RDB cells respectively). However, we observed SBS was more efficient to induce apoptosis in EPG than RDB cells. We strongly suggest SBS be considered as a prospective anticancer agent or in formulation of complementary medication to treat and prevent gastric cancers. Abstract : We found that SBS decreased cell viability, induced apoptosis, and reduced survival gene expression in treated EPG and RDB cells. However, we observed SBS was more efficient to treat EPG than RDB cells. We strongly suggest SBS be considered as a prospective anticancer agent or in formulation of food functional additives to treat and prevent gastric cancers.